Reflections on the development of an efl reading programme for middle school students of varied levels of english (2003)
This personal-experience article attempts to share with the reader an EFL reading and grammar programme that was designed in 2002 for a group of 12 to 14-year olds (6th and 7th graders) whose English levels varied from almost nil to semiconversational. Multi-levels of English in any given group present a considerable challenge to either the EFL or ESL teacher, needless to say. More than one of these students exhibited evidence of a learning disability, not only in L2 but in L1 as well. For instance, transposition of letters (b instead of d and vice versa) in both languages, poor spelling in L1 and L2, and in L2, writing on the level of a second or third- grade native speaker. A considerable number of these students had been forced to leave other, larger schools for academic and/or disciplinary reasons. So, this teacher swallowed then rolled up his sleeves to go to work (in fear of what the year would bring?). In other words, the teacher accepted the challenge. Key words: English-Teaching High School-Programs, Reading-Teaching-Programs, Books and Reading for Children-Teaching High School-Programs Este artículo de experiencia personal tiene como objetivo dar a conocer al lector un programa de EFL sobre lectura y gramática que fue diseñado en 2002 para un grupo de niños entre los 12 y 14 años de edad (grados 6 y 7), los cuales tenían niveles de inglés que variaban entre cero conocimiento del idioma y semi-conversacional. Los multi-niveles en inglés en cualquier grupo presentan un desafío considerable para el profesor de EFL o ESL. Adicionalmente, más de un estudiante demostró tener problemas de aprendizaje no sólo en L2 sino en L1. Por ejemplo, la transposición de letras (b en vez de d o viceversa) en ambos idiomas, pobre ortografía en L1 y L2 y en L2 la escritura en un nivel igual al de un estudiante nativo que cursa segundo o tercero de primaria. Un número considerable de estudiantes han sido obligados a abandonar otros colegios grandes por razones académicas y/o disciplinarias. Así que me alisté para ir a trabajar, remangándome la camisa (¿quizá con el miedo de pensar qué traería el nuevo año?). En otras palabras, acepté el desafío. Palabras claves: Inglés-Enseñanza secundaria-Programas, Lectura-Enseñanza- Programas, Libros y lecturas para niños-Enseñanza secundaria-programas